Drosophila Wee1 kinase rescues fission yeast from mitotic catastrophe and phosphorylates Drosophila Cdc2 in vitro. - Campbell, S D (1995)
Cdc2 kinase activity is required for triggering entry into mitosis in all known eukaryotes. Elaborate mechanisms have evolved for regulating Cdc2 activity so that mitosis occurs in a timely manner, when preparations for its execution are complete. In Schizosaccharomyces pombe, Wee1 and a related Mik1 kinase are Cdc2-inhibitory kinases that are required for preventing premature activation of the mitotic program. To identify Cdc2-inhibitory kinases in Drosophila, we screened for cDNA clones that rescue S. pombe wee1- mik1- mutants from lethal mitotic catastrophe. One of the genes identified in this screen, Drosophila wee1 (Dwee1), encodes a new Wee1 homologue. Dwee1 kinase is closely related to human and Xenopus Wee1 homologues, and can inhibit Cdc2 activity by phosphorylating a critical tyrosine residue. Dwee1 mRNA is maternally provided to embryos, and is zygotically expressed during the postblastoderm divisions of embryogenesis. Expression remains high in the proliferating cells of the central nervous system well after cells in the rest of the embryo have ceased dividing. The loss of zygotically expressed Dwee1 does not lead to mitotic catastrophe during postblastoderm cycles 14 to 16. This result may indicate that maternally provided Dwee1 is sufficient for regulating Cdc2 during embryogenesis, or it may reflect the presence of a redundant Cdc2 inhibitory kinase, as in fission yeast.